Identification of potential key circular RNAs related to cognitive impairment after chronic constriction injury of the sciatic nerve - Liu, Changliang; Gao, Rui; Tang, Yidan; Chen, Hai; Zhang, Xueying; Sun, Yalan; Zhao, Qi; Lv, Peilin; Wang, Haiyang; Ye-Lehmann, Shixin; Liu, Jin; Chen, Chan (Frontiers in Neuroscience, 2022)
Chronic neuropathic pain is commonly accompanied by cognitive impairment. However, the underlying mechanism in the occurrence of cognitive deficits under constant nociceptive irritation remains elusive. Herein, we established a chronic neuropathic pain model by chronic constriction injury (CCI) of the unilateral sciatic nerve in rats. Behavioral tests indicated that CCI rats with long-term nociceptive threshold decline developed significant dysfunction of working memory and recognitive memory starting at 14 days and lasting for at least 21 days. Afterward, circRNA expression profiles in the hippocampus of CCI and sham rats were analyzed via high-throughput sequencing to explore the potential key factors associated with cognitive impairment induced by ongoing nociception, which showed 76 differentially expressed circRNAs, 39 upregulated and 37 downregulated, in the CCI group. These differentially expressed circRNA host genes were validated to be primarily associated with inflammation and apoptotic signaling pathways according to GO/KEGG analysis and the circRNA-miRNA-mRNA network, which was also confirmed through the analysis of neuroinflammation and neuronal apoptosis. Consequently, we assumed that enhanced neuroinflammation and neuronal apoptosis might act as potential regulators of cognitive impairment induced by chronic neuropathic pain. The identification of the regulatory mechanism would provide promising clinical biomarkers or therapeutic targets in the diagnostic prediction and intervention treatment of memory deficits under neuropathic pain conditions.